Rapid enlargement of an intracranial germ cell tumor after gonadotropin hormone therapy. (September 2016) - Sasagawa, Yasuo; Tachibana, Osamu; Nakagawa, Athushi; Nakada, Satoko; Nojima, Takayuki; Koya, Daisuke; Iizuka, Hideaki
Highlights: We report an unusual course of an intracranial germ cell tumor (iGCT). The tumor showed rapid growth after human chorionic gonadotropin (hCG) therapy. iGCT may be at risk of progression during hCG therapy. Careful monitoring is required for a patient with iGCT who receives this therapy. Abstract: We report a case of an intracranial germ cell tumor (iGCT) that showed rapid enlargement after human chorionic gonadotropin (hCG) hormone therapy for pituitary hypogonadism. A 16-year-old boy presented with headache and was diagnosed with a suprasellar tumor. He was initially observed without surgery. Intranasal desmopressin therapy was started for central diabetes insipidus, but there was no change in the tumor size on MRI. The diagnosis of the tumor remained unknown for 4 years. Levels of serum gonadotropin hormones (follicle–stimulating and luteinizing hormone) and testosterone progressively decreased, and the patient developed pituitary hypogonadism and complained about his undeveloped beard, lack of underarm hair, and erectile dysfunction. Intramuscular gonadotropin injection (hCG 5000 U × 2/week) was started at age 20. Eight months after the first gonadotropin injection, the MRI showed tumor growth with vivid enhancement. Craniotomy was performed and the tumor was partially resected. The histological diagnosis was immature teratoma. After surgery, the patient was treated with 5 cycles of chemotherapy with carboplatin and etoposide. He also received radiation therapy of 50 Gy (20 Gy tumor bed and 30 Gy whole ventricles) to the residual tumor, after which the tumor decreased in size. We postulate that iGCT may be at risk of progression during hCG hormone therapy. Thus, careful monitoring is required for a patient with iGCT who receives this therapy.